Diagnóstico dos principais problemas existentes no transporte de produtos perigosos - Vieira, Bernadeth Macedo (2006)
The present work searchs to trace a diagnosis of the main irregularities practised in the transport of dangerous products through an analysis of the main irregularities practised in the federal highways, using as tool the statistical data raised together to the Federal Road Policy and the depositions of a sampling of Policemen who had contributed with its practical experiences. Aiming at to interact the three involved segments, or either, dispatcher, transporter and fiscalization, workshops still searched the manifestations presented in two that they had counted on the participation of the legislators of the ANTT, technician and entrepreneurs of the transport sector. Statisticians prove that the road transport of dangerous products has generated diverse risks to the man and the environment, having caused material damages, as well as the a health and to the life. Being common to identify the practical one of the transport of these products without the fulfilment of the effective legal requirements. Although the legal devices that regulate the subject in question are complex and of matrix strict technician, making it difficult its interpretation on the part of the operational user, the results had demonstrated that the practised irregularities more are related the operational deficiencies, being distinguished with bigger amount of cultivated fines, representing 38%, the applied ones to kits of emergency and identified EPI's being as more frequent irregularity the lack of some itens that they integrate kits and 26% for the emergency fiches, being more common to find them it are of the standard established for the inadequate norm Brazilian or the carried product.